Ido Koch, Oded Lipschits & Omer Sergi (eds.), From Nomadism to Monarchy? Revisiting the Early Iron Age Southern Levant. - Thomas , Zachary (Antiguo Oriente, 2024)
This volume, deriving from a conference at Tel Aviv University in 2017, comes several decades on (and derives its title) from the volume From Nomadism to Monarchy, a major milestone in the archaeological and historical study of early Israel and the southern Levant west of the Jordan river during the early Iron Age. That earlier volume was particularly significant in making new strides in research based on then-recent archaeological fieldwork (primarily surveys) in the central highlands and partly in the Galilee, as well as an earlier generation of excavations in the lowland areas.